2000
DOI: 10.1046/j.1469-8137.2000.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal deployment of crop roots in CO2‐enriched environments

Abstract:  Growth of crops in CO# -enriched atmospheres typically results in significant changes in root growth and development. Increased root carbohydrates stimulate root growth either directly (functioning as substrates) or indirectly (functioning as signal molecules) by enhancing cell division or cell expansion, or both. Although highly variable, the literature suggests that, generally, initiation and stimulation of lateral roots is favored over the elongation of primary roots, leading to more highly branched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 119 publications
3
81
0
Order By: Relevance
“…Fine roots at the soil surface may be beneficial in capturing water after a dry soil is rewetted (Kosola & Eissenstat 1994). Several experiments suggest that crop plants in a higher CO 2 atmosphere will have larger root systems that are more highly branched, especially at shallow depths, and this should increase the capacity for resource acquisition, but at lower efficiency (Pritchard & Rogers 2000). CO 2 enrichment of a grassland community led to an upward shift in root length density with a greater proportion of roots in the top 6 cm soil layer (Arnone et al .…”
Section: Fine-root Proliferation and Implications For Whole-plant Watmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine roots at the soil surface may be beneficial in capturing water after a dry soil is rewetted (Kosola & Eissenstat 1994). Several experiments suggest that crop plants in a higher CO 2 atmosphere will have larger root systems that are more highly branched, especially at shallow depths, and this should increase the capacity for resource acquisition, but at lower efficiency (Pritchard & Rogers 2000). CO 2 enrichment of a grassland community led to an upward shift in root length density with a greater proportion of roots in the top 6 cm soil layer (Arnone et al .…”
Section: Fine-root Proliferation and Implications For Whole-plant Watmentioning
confidence: 99%
“…1999;Pritchard & Rogers 2000). In general, elevated [CO 2 ] increases plant biomass, root mass and total leaf area (Rogers, Runion & Krupa 1994;Curtis & Wang 1998) and alters leaf net photosynthetic rates, stomatal conductance and water-use efficiency (WUE) (Gunderson & Wullschleger 1994;Saxe, Ellsworth & Heath 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In an annual crop system, the important research questions are more likely to revolve around root deployment and resource capture rather than equilibrium responses and C flux (Fitter et al, 1991). Root turnover is likely to be impacted by CO # differently in annual versus perennial plants (Pritchard & Rogers, 2000).…”
Section:      mentioning
confidence: 99%
“…In discussing the responses of crop roots to elevated CO # , Pritchard & Rogers (2000) emphasize the importance of cell expansion and cell division and suggest that a key to understanding how root growth will change in a high-CO # environment is to understand how carbohydrates, especially sucrose, functions both as a substrate for growth and as a regulatory molecule. From this perspective, they review the literature and conclude that roots in a high CO # environment will be larger and more highly branched, but less efficient in nutrient and water uptake (also see Berntson & Bazzaz, 1996 ;Rogers et al, 1999).…”
Section:      mentioning
confidence: 99%
“…With regard to increased root length under elevated CO 2 environment, it is reported that the responses of roots to CO 2 are dependent on experimental conditions (Ceulemans & Mousseau 1994). When the plants exposed to increased CO 2 , root have observed to become more numerous, longer, thicker and faster growing in crops (Chandhuri et al 1990) with increased root length in many plant species (Norby 1994, Pritchard & Rogers 2000, Bernecchi et al 2000. Lengths and volumes of tap root and fine roots were higher for CO 2 enhanced cotton plants (Rogers et al 1993).…”
Section: Results and Discussion A) Response Of Azadirachta Indica Tomentioning
confidence: 99%